in $A^*(Y_2 \to Y)$ where $f_2 : Y_2 \to X_2$ is the base change of $f$.
Proof. Let $\alpha \in A_ k(X)$. We may write
with $\alpha _ i \in A_ k(X_ i)$; we are omitting the pushforwards by the closed immersions $X_ i \to X$. The reader then checks that $c'_ p(E_2) \cap \alpha = c_ p(E_2) \cap \alpha _2$, $c \cap c'_ p(E_2) \cap \alpha = c \cap c_ p(E_2) \cap \alpha _2$, $c \cap \alpha = c \cap \alpha _1 + c \cap \alpha _2$, and $c'_ p(Lf_2^*E_2) \cap c \cap \alpha = c_ p(Lf_2^*E_2) \cap c \cap \alpha _2$. We conclude by Lemma 41.41.3. $\square$
Post a comment
Your email address will not be published. Required fields are marked.
In your comment you can use Markdown and LaTeX style mathematics (enclose it like
$\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).
All contributions are licensed under the GNU Free Documentation License.